Increased tissue concentrations of 5-hydroxytryptamine in the duodenal mucosa of patients with coeliac disease. Issue 11 (November 1977) - Challacombe, D N; Dawkins, P D; Baker, P
Abstract : Tissue concentrations of 5-HT have been measured in the duodenal mucosa of adults and children with coeliac disease and were found to be significantly higher than those from a control group. This finding may be associated with hyperactivity or hyperplasia of enterochromaffin (EC) cells in the duodenum of patients with coeliac disease and could also be directly related to described abnormalities of 5-HT metabolism in this disease.